A novel blue-emitting Eu2+-doped chlorine silicate phosphor with a narrow band for illumination and displays: structure and luminescence properties. Issue 24 (30th April 2019) - Wei, Qi; Zhou, Xufeng; Tang, Zuobin; Wang, Xicheng; Wang, Yuhua
Abstract : A novel silicate-based phosphor Ba5 SiO4 Cl6 :Eu 2+ (BSOC:Eu 2+ ) was successfully designed and investigated through the solid-state method. Abstract : A novel silicate-based phosphor Ba5 SiO4 Cl6 :Eu 2+ (BSOC:Eu 2+ ) was successfully designed and investigated through the solid-state method. The crystal structure, band structure, photoluminescence and cathodoluminescence characteristics were investigated in detail. Under excitation at 345 nm, a narrow blue emission band with a peak at 440 nm (FWHM ∼ 32 nm) could be observed. Moreover, BSOC:Eu 2+ showed higher color purity when compared with a commercial BAM phosphor. Under sustained low-voltage electron-beam excitation, the BSOC:Eu 2+ phosphor exhibited blue emission with distinguished degradation resistance and perfect colour stability. By combining the BSOC:Eu 2+ blue phosphor with green and red phosphors and an n-UV chip, a pc-WLED with a high color rendering index and low correlated color temperature was obtained. The results show that the BSOC:Eu 2+ phosphor has wide application prospects in n-UV LED applications and FED devices.